Hurricane Mitch - The gender Effects of Coping and Crises - Correia, Maria (World Bank, Washington, DC, 2012)
Decentralization holds a lot of promise, but whether it improves public service delivery depends on the institutional arrangements governing its implementation. Several conditions must be met before the full benefits of decentralization can be reaped. First, for decentralization to increase allocative and productive efficiency, local governments need to have the authority to respond to local demand as well as adequate mechanisms for accountability. Because granting authority without accountability can lead to corruption and lower productive efficiency, decentralization needs to be accompanied by reforms that increase the transparency and accountability of local government. Second, functions need to be devolved to a low enough level of government for allocative efficiency to increase as a result of decentralization. Low-level governments are likely to be aware of local preferences and, if able to do so, are likely to adjust service delivery accordingly. Third, citizens should have channels to communicate their preferences and get their voices heard in local governments. But the existence of such channels is not enough. To effectively influence public policies and oversee local governments, citizens need to have information about government policies and activities. The media play a crucial role in this area.